Does a tonsillectomy indicated according to the German S2k guideline affect short-term quality of life in adults? - Plath, Michaela; Sand, Matthias; Behnen, Kjell; Plath, Karim; Baumann, Ingo (European archives of oto-rhino-laryngology and head & neck, 2023)
Tonsillectomy (TE) for recurrent tonsillitis (RT) is one of the most common surgical interventions. Since 2015, the indication criteria for TE have become much stricter (German S2k guideline). Patient-reported outcome measures (PROMs) of short-term quality of life (QoL) after TE have not yet been investigated.